An approach to economic dynamics in 5th-Century internal Africa : the contribution of the study of fine ceramic ware from the city of Ammaedara (Haïdra, Tunisia) - (:unkn) unknown (My University, 2023)
Over the last few decades, advances in studies of the African economy have made it possible to qualify models that had long been accepted. Until recently, most of our knowledge came from the products of the great Mediterranean trade, amphora and African Red Slip wares, but work carried out in the inner regions of Africa has demonstrated the existence of an intra-provincial trade fuelled by continental ceramic productions, from the second half of the 2nd century to at least the Vandal period.This economic pattern, which has been highlighted by surveys and rare excavations, still raises many questions about the trade routes to and within these regions. The study of fine wares from the ancient city of Ammaedara/Haïdra (Tunisian High Steppes) provides new data on economy and patterns of consumption Inland regions of Roman Africa.
Keywords: African Research